Analytical Shifts in Contemporary Literary Studies: From Digital Humanities to New Directions in Indonesian Literature - Andri Wicaksono; Dany Ardhian; Sultan Tirta Mujtaba (Badan Pengembangan dan Pembinaan Bahasa, 2026)
Contemporary literary studies are undergoing significant analytical transformations alongside the increasing use of computational methods and digital humanities. This article aims to examine the epistemological tensions emerging from these transformations and to formulate a critical analytical framework for contemporary literary studies. The study employs a critical literature review combining narrative and systematic review approaches. Data were collected from academic publications indexed in Scopus, Web of Science, JSTOR, Google Scholar, and major academic publishers focusing on digital humanities, distant reading, critical digital studies, representation theory, and intertextuality. The collected data were analyzed through critical interpretation and thematic synthesis to identify major conceptual debates and methodological tendencies. The study finds that computational literary approaches expand the scale of textual exploration but also risk reducing literary meaning into statistical abstraction and reproducing representational bias when detached from critical reflection. Based on these findings, the article proposes a layered critical analytical model integrating computational exploration, hermeneutic interpretation, and critical reflection. The framework is further contextualized within Indonesian literary studies characterized by multilingualism, digital literary practices, and diverse cultural traditions. This study contributes to the development of contemporary literary studies by offering an integrative framework that connects scale, interpretation, and power relations in the digital era. Abstrak Kajian sastra kontemporer mengalami transformasi analitik yang signifikan seiring meningkatnya penggunaan metode komputasional dan humaniora digital. Artikel ini bertujuan mengkaji ketegangan epistemologis yang muncul dari transformasi tersebut serta merumuskan kerangka analitik kritis bagi kajian sastra kontemporer. Penelitian ini menggunakan metode studi pustaka kritis yang mengombinasikan pendekatan narrative review dan systematic synthesis. Data penelitian diperoleh dari publikasi akademik yang terindeks Scopus, Web of Science, JSTOR, Google Scholar, serta berbagai penerbit akademik utama yang membahas humaniora digital, distant reading, kajian digital kritis, teori representasi, dan intertekstualitas. Data dianalisis melalui interpretasi kritis dan sintesis tematik untuk mengidentifikasi perdebatan konseptual dan kecenderungan metodologis utama. Hasil penelitian menunjukkan bahwa pendekatan komputasional dalam kajian sastra mampu memperluas skala eksplorasi teks, tetapi juga berisiko mereduksi makna sastra menjadi abstraksi statistik dan mereproduksi bias representasi apabila tidak disertai refleksi kritis. Berdasarkan temuan tersebut, artikel ini mengajukan model analitik kritis berlapis yang mengintegrasikan eksplorasi komputasional, interpretasi hermeneutik, dan refleksi kritis. Kerangka ini kemudian dikontekstualisasikan dalam kajian sastra Indonesia yang bercirikan multibahasa, praktik sastra digital, dan keragaman tradisi budaya. Penelitian ini berkontribusi pada pengembangan kajian sastra kontemporer melalui kerangka integratif yang menghubungkan skala, interpretasi, dan relasi kuasa di era digital.